2019
DOI: 10.1097/spv.0000000000000668
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of Women With Pelvic Floor Disorders to Use Mobile Technology to Communicate With Their Health Care Providers

Abstract: Objectives: To assess willingness of women with pelvic floor disorders to adopt non-traditional mobile communication methods with health care providers. Methods: Cross-sectional study of women with pelvic floor disorders. Women completed a survey regarding what technology they owned, how they utilized it and their willingness to use technology to communicate with providers. Results: Overall mobile technology ownership was high; however, older women were significantly less likely to own a smart phone (75%) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 22 publications
0
25
1
Order By: Relevance
“…A 2015 survey by the Pew Research Center reported that 60% American adults have a smartphone with only those age 65 and older (30%) and those who did not complete a high school education (41%) falling below majority ownership 17 . In a recent survey of 200 women with pelvic floor disorders, 92% women overall and 75% women age 65 years and older owned a smartphone 18 . In this study, though younger women were more likely than older women to use technology to track health‐related information, the utilization of smartphone “apps” for health‐related reasons was high across all age groups.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…A 2015 survey by the Pew Research Center reported that 60% American adults have a smartphone with only those age 65 and older (30%) and those who did not complete a high school education (41%) falling below majority ownership 17 . In a recent survey of 200 women with pelvic floor disorders, 92% women overall and 75% women age 65 years and older owned a smartphone 18 . In this study, though younger women were more likely than older women to use technology to track health‐related information, the utilization of smartphone “apps” for health‐related reasons was high across all age groups.…”
Section: Discussionmentioning
confidence: 58%
“…17 In a recent survey of 200 women with pelvic floor disorders, 92% women overall and 75% women age 65 years and older owned a smartphone. 18 In this study, though younger women were more likely than older women to use technology to track health-related information, the utilization of smartphone "apps" for health-related reasons was high across all age groups. In fact, it has been noted that older adults have positive attitudes about using technology for health care with the perception of a benefit and ease of use as influential factors for older adults to use mHealth (mobile health) apps.…”
Section: Discussionmentioning
confidence: 58%
“…Eleven studies reported data on the application of telehealth in prostate cancer (PCa) [17,20,26,30,34,35,37,39,42,45,48], three studies in the diagnosis of patients with hematuria [31,40,43], six studies in the management of urinary stone disease [9][10][11]44,46,47], 14 studies in the management of urinary incontinence (UI) [12,22,23,25,27,28,32,33,36,38,[49][50][51] five studies in urinary tract infections (UTIs) [15,16,19,21,53], and six studies in other urological conditions [11,14,18,24,41]; 12 reports were randomized controlled trials (RCTs) [12,17,18,22,[25]…”
mentioning
confidence: 99%
“… To observe all norms and rules contained in the Codes of Ethics and Deontology of Physiotherapy and take into consideration that this may be influenced by each country’s specifics as well as specific regulations and/or standards of service involved and possible new regulations related to the pandemic, even when using digital physiotherapy [ 12 ]. To consider cultural aspects, technological and personal limitations on the use of technology, patient availability and access to technology, and familiarity of physiotherapists and patients with technological tools [ 13 ]. To choose the most appropriate digital method, considering the specific case to be treated as well as patient access and preferences.…”
Section: Resultsmentioning
confidence: 99%
“…To consider cultural aspects, technological and personal limitations on the use of technology, patient availability and access to technology, and familiarity of physiotherapists and patients with technological tools [ 13 ].…”
Section: Resultsmentioning
confidence: 99%